APPLICATION OF MACHINE LEARNING TO FORM A KNOWLEDGE BASE OF INTELLIGENT INFORMATION SYSTEMS - Abdullaeva Ozoda Safibullaevna; Abdullajonova Nurzoda Nurmakhamadovna (Research Focus International Scientific Journal, 2025)
In recent years, the integration of artificial intelligence (AI) and intelligent information systems (IIS) into various sectors has been accelerating, particularly in education. These advancements aim to improve the quality of education through automation, intelligent analysis, and dynamic decision-making. One key area where intelligent information systems have shown significant potential is in psychological diagnostics for students. These systems can play a vital role in helping assess students’ abilities, provide personalized learning paths, and assist in career guidance, fostering better educational outcomes. This article outlines the stages of developing an Intelligent Information System for Psychological Diagnostics, which aims to assess students' psychological state, cognitive abilities, and personal interests. This system will also provide the necessary data to guide students in making informed academic and career decisions. Below, we explore the stages of development and functionality of this system, focusing on the benefits it can bring to both educators and students.